MORAL POLITIK CANAKYA DALAM ARTHASASTRA - Ni Made Sumaryani (Veda Jyotih: Jurnal Agama dan Sains, 2022)
A leader needs to have political morals in running the government, so as not to abuse the authority and power that causes suffering for the people. In many cases, they use their control to reap personal benefits while ensnaring the people. This article uses a qualitative method with a literature study approach related to Canakya's political morals. Canakya presents politics in a complex way in his Arthasastra. He did not treat politics arbitrarily with power but formed a great leadership candidate by prioritizing the happiness and welfare of his people. For the sake of its continuity, this leadership task must be carried out for every born ksatriya. Katriya is not just birth, and profession but ksatriya is attitude, principle, stance, character, and all of them combined.